Case Studies—Voices of Students and Teachers - Douvlou, Elena; Tzoumis, Kelly; Fernandes, Giséle Manganelli [UNESP]; Shanahan, John; Ginger Hofman, Nila; Sinha Deshpande, Shweta; Klimas, Christie A.; Almeida, Odair [UNESP]; Chapin, John R.; Rossette-Crake, Fiona; Rubin, Jon; Chatterji, Tuli; et al. (My University, 2023)
In this section the reader will first find abstracts of six faculty COIL course case studies. All but one of these case studies were jointly written by pairs of COILing teachers based in different countries who completed a COIL exchange during 2018 and/or 2019. In most of these cases, one of the partners was based in the United States, with partners located in Greece, Brazil, India, or France. One case study is retrospective and explores the evolution of a COIL-like media course involving partners in different countries over several years, between 2002 and 2011.